Neurophysiological Effects of Chronic Indoor Environmental Toxic Mold Exposure on Children - Ebere C. Anyanwu; Andrew W. Campbell; Aristo Vojdani (The Scientific World Journal)
The phenomenon of building-related diseases is attracting much research interest in recent years because of the extent to which it affects people with compromised immune systems, especially children. In this study, we reported the neurological findings in children who attended our Center because of chronic exposure to toxic molds. Clinical neurological and neurobehavioral questionnaires were administered with the cooperation of the childrens parents. The children then underwent a series of neurophysiological tests including electroencephalogram (EEG), brainstem evoked potential (BAEP), visual evoked potential (VEP), and somatosensory evoked potential (SSEP). The results showed high levels of abnormalities in the analysis of the subjective responses derived from the questionnaires. The EEG examination was abnormal in seven out of ten of the patients compared to the controls with only one in ten with episodes of bihemispheric sharp activity. In all the patients, there was frontotemporal theta wave ativity that seemed to indicate diffuse changes characteristic of metabolic encephalopathies. Also, there was highly marked 1 to 3 Hz delta activity that was asymmetrical in the right hemisphere of the brain in three out of ten patients. The waveforms of BAEP showed abnormalities in 90% of the patients with both 15’ and 31’ check sizes compared to none in the controls. There were significant delays in waveform V in a majority of the patients representing dysfunctional cognitive process and conductive hearing loss in both ears. VEP showed clear abnormalities in four in ten of the patients with P100 amplitudes and latencies decreased bilaterally. In all the patients, there was slowing of conduction in the right tibial at an average of 36.9 ms and there was significant decrease in amplitude of response at the proximal stimulation site. Sensory latencies obtained in the median, ulnar, and sural nerves bilaterally showed abnormalities in five out of ten compared to none in the controls. The median, ulnar, and sural sensory potentials were abnormal in six out of ten patients. There was prolongation of the median distal sensory latencies bilaterally at an average of 4.55 ms on the right and an average of 6.10 ms on the left as compared to the ulnars of 2.55 ms bilaterally. There was no abnormality in the controls. These findings represent evidence of diffuse polyneuropathy to which three patients demonstrated borderline slow motor conduction at an average of 41.1 ms. Overall, the objective neurophysiological measurements (EEG, BAEP, VEP, and SSEP) were abnormal, indicating significant neurological deficits in all the patients. Our findings revealed the extent to which toxic molds can affect the neurological and behavioral status of children. Further work should be encouraged in this regard.